Albuminuria Increases the Risks for Both Alzheimer Disease and Vascular Dementia in Community‐Dwelling Japanese Elderly: The Hisayama Study. Issue 2 (20th January 2018) - Takae, Keita; Hata, Jun; Ohara, Tomoyuki; Yoshida, Daigo; Shibata, Mao; Mukai, Naoko; Hirakawa, Yoichiro; Kishimoto, Hiro; Tsuruya, Kazuhiko; Kitazono, Takanari; Kiyohara, Yutaka; Ninomiya, Toshiharu
Abstract : Background: Epidemiologic evidence has emerged to reveal an association of albuminuria and low estimated glomerular filtration rate (eGFR) with dementia, but the findings are inconsistent. In addition, there are limited studies addressing the association between albuminuria and Alzheimer disease (AD). Methods and Results: A total of 1562 community‐dwelling Japanese subjects aged ≥60 years without dementia were followed up for 10 years. The outcomes were incidence of all‐cause dementia and its subtypes, namely, AD and vascular dementia (VaD). The hazard ratios for the outcomes were estimated according to urine albumin–creatinine ratio (UACR) and eGFR levels using a Cox proportional hazards model. During the follow‐up, 358 subjects developed all‐cause dementia (238 AD and 93 VaD). Higher UACR level was significantly associated with greater multivariable‐adjusted risks of all‐cause dementia (hazard ratios [95% confidence intervals]: 1.00 [reference], 1.12 [0.78–1.60], 1.65 [1.18–2.30], and 1.56 [1.11–2.19] for UACR of ≤6.9, 7.0–12.7, 12.8–29.9, and ≥30.0 mg/g, respectively), AD (1.00 [reference], 1.20 [0.77–1.86], 1.75 [1.16–2.64], and 1.58 [1.03–2.41], respectively), and VaD (1.00 [reference], 1.03 [0.46–2.29], 1.94 [0.96–3.95], and 2.19 [1.09–4.38], respectively). On the other hand, lower eGFR level was marginally associated with greater risk of VaD, but not AD. Subjects with UACR ≥12.8 mg/g and eGFR of <60 mL/min per 1.73 m 2 had 3.3‐fold greater risk of VaD than those with UACR <12.8 mg/g and eGFR of ≥60 mL/min per 1.73 m 2 . Conclusions: Albuminuria is a significant risk factor for the development of both AD and VaD in community‐dwelling Japanese elderly. Moreover, albuminuria and low eGFR are mutually associated with a greater risk of VaD.